Magnesium alloy surface multi-response self-repairing long-acting coating and preparation method and application thereof
By constructing a self-healing coating with a multi-layer structure on the surface of magnesium alloy, the combination of Mg(OH)2, PDA and PCL is used to solve the problem of easy damage to the magnesium alloy coating, achieving long-term anti-corrosion and multi-function protection.
Patent Information
- Application Number
- CN202411906560.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Due to its high electronegativity and corrosion sensitivity, magnesium alloys are prone to damage and cracking during the anti-corrosion process, resulting in a degradation of anti-corrosion performance.
A self-healing long-acting coating with multiple responses on the surface of magnesium alloy is used to generate Mg(OH)2 through hydrothermal reaction, electrophoresis deposits polydopamine (PDA), and spin-coated polycaprolactone (PCL) layer containing core-shell structure nanoparticles AgNR@MSN@DA on the surface of the PDA to realize the self-healing function of the coating.
This coating not only achieves long-term anti-corrosion functions, but also has the functions of deicing and marine anti-fouling, and achieves a lasting and stable protection effect through multiple response mechanisms (Mg2+, pH and NIR).
Smart Images

Figure CN119733659A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of surface modification, and in particular to a self-repairing long-lasting coating with multiple responses on the surface of a magnesium alloy, and a preparation method and application thereof. Background Art
[0002] Magnesium alloys have high strength and high toughness. At the same time, their low density makes them the lightest and strongest material among structural alloys. This makes it possible to design lighter engineering systems and reduce energy consumption. Magnesium alloys are also used as lightweight metals in the transportation and electronics industries due to their electromagnetic shielding properties, heat dissipation capabilities and machinability. In recent years, magnesium alloys have also shown great potential in a variety of new applications from batteries to biomedical products. However, due to their high electronegativity, the corrosion sensitivity of magnesium alloys has always been an obstacle to their further application in various fields.
[0003] There are two feasible ways to regulate the corrosion sensitivity of magnesium alloys: developing new corrosion-resistant magnesium alloys and surface modification of magnesium alloys. Coating preparation is one of the most effective means of metal corrosion protection. For magnesium alloys, metal coatings are prone to galvanic corrosion. The corrosion resistance of inorganic coatings alone is limited, and the bonding strength of pure organic coatings with the substrate is poor. Therefore, inorganic and organic coatings are usually combined. However, the coating will inevitably be damaged and cracked during the anti-corrosion process, resulting in a decrease in anti-corrosion performance. Therefore, it is necessary to develop a long-lasting coating with the function of repairing damage. This coating with the function of repairing damage is divided into functional repair coatings and shape repair coatings. Functional repair coatings restore the protective ability of the coating by loading corrosion inhibitors; shape repair coatings repair the morphology and structure of the coating through reversible reactions of polymers, chemical bond reorganization and shape memory effects. Long-lasting coatings with the function of repairing damage can repair the surface damage of the coating in time when the coating is damaged, and restore the long-term protective effect of the coating. It has great research value and economic benefits in the protection of magnesium alloys. Summary of the invention
[0004] In view of the shortcomings of the above-mentioned background technology, the present invention mainly solves the problem that the coating in the prior art will inevitably be damaged and cracked during the anti-corrosion process, resulting in a decrease in anti-corrosion performance. The present invention provides a self-repairing long-lasting coating with multiple responses on the surface of a magnesium alloy and a preparation method and application thereof. The method firstly hydrothermally reacts the magnesium alloy to obtain an in-situ grown Mg(OH) 2 , the Mg(OH) 2 The coating is grown in situ, has excellent bonding strength, and releases warning signals before the magnesium alloy substrate is about to be corroded. 2+ and OH - , stimulating the function of repairing corrosion cracks; then in Mg(OH) 2A layer of PDA is deposited on the surface by electrophoresis. PDA can adhere to the upper and lower layers in the middle to enhance the bonding force between the coatings. PDA can also 2+ Chelation enhances the anti-corrosion performance of the coating; finally, a layer of PCL containing core-shell structured nanoparticles AgNR@MSN@DA is spin-coated on the surface of PDA. When the coating is damaged and the magnesium alloy is corroded, OH is released. - By enhancing the alkalinity of the environment, PCL will decompose in an alkaline environment to release DA in the nanoparticles AgNR@MSN@DA. DA will polymerize into PDA in response to the alkaline environment, and re-form strong hydrogen with PCL or re-polymerize with the electrophoretically deposited intermediate layer PDA to repair the cracks. At the same time, NIR irradiation is applied, and the synergistic response of AgNR and PDA to the photothermal effect is used to increase the temperature of the PCL coating and melt and flow to repair the cracks. In this way, a Mg(OH)-based 2 Early warning, response Mg 2+ , pH and NIR to achieve a long-lasting and stable multi-protection inorganic-organic composite coating with good bonding force. This coating not only has a long-lasting anti-corrosion function, but also has the functions of de-icing and marine anti-fouling.
[0005] The first object of the present invention is to provide a method for preparing a multi-responsive self-repairing long-lasting coating on a magnesium alloy surface, comprising the following steps: The hydrothermal reaction was carried out on the surface of magnesium alloy to obtain in-situ grown Mg(OH) 2 ; In situ grown Mg(OH) 2 Polydopamine was electrophoretically deposited on the surface; preparing nanoparticles of silver nanorods wrapped in silica and loaded with dopamine; uniformly dispersing the nanoparticles in a polycaprolactone solution to obtain a polycaprolactone solution containing the nanoparticles; A polycaprolactone solution containing nanoparticles is coated on polydopamine to prepare a multi-responsive self-repairing long-lasting coating on the surface of a magnesium alloy.
[0006] Preferably, when the hydrothermal reaction is carried out on the surface of the magnesium alloy, the concentration of the hydrothermal solution is 0.001-0.1 g / mL of NaOH solution, the temperature is 80-160° C., and the reaction time is 1-12 h.
[0007] Preferably, the in situ grown Mg(OH) 2 When polydopamine is electrophoretically deposited on a substrate, the electrophoresis solution is a 1-10 mg / mL DA solution, and the solvent of the DA solution is deionized water; During electrophoretic deposition, the distance between the anode and cathode is 8-15 mm and the applied current is 2-6 mA / cm 2 The electrophoretic deposition time is 1-10 min; the in-situ grown Mg(OH) 2of magnesium alloy as cathode.
[0008] Preferably, in the polycaprolactone solution containing nanoparticles, the polycaprolactone concentration is 1-20 wt %; the nanoparticle concentration is 1-30 mg / mL; The polycaprolactone solution is prepared by dissolving polycaprolactone in one or more of dichloromethane, chloroform and acetone.
[0009] Preferably, when the polycaprolactone solution containing nanoparticles is coated on the polydopamine, the coating is performed by spin coating, wherein during the spin coating, the spin coating is stopped for 10 to 90 seconds at a low speed stage of 200 to 800 rpm and a high speed stage of 1000 to 3000 rpm.
[0010] Preferably, the silica-wrapped silver nanorods and dopamine-loaded nanoparticles include nanoparticles with silica as a shell, silver nanorods as a core, and dopamine as a pore carrier; wherein the length of the silver nanorods is 100-120 nm, and the aspect ratio is 4.16±0.13; The thickness of the silica shell is 10-80 nm; The dopamine loading rate is 5-95% by mass.
[0011] Preferably, before the hydrothermal reaction on the magnesium alloy surface, the magnesium alloy surface is also pretreated, including: polishing the magnesium alloy surface with sandpaper, and then ultrasonically treating the magnesium alloy with acetone and anhydrous ethanol for 5 to 15 minutes respectively.
[0012] Preferably, the magnesium alloy includes AZ series, ZK series, WE series or JDBM magnesium alloy.
[0013] The second object of the present invention is to provide a self-repairing long-lasting coating with multiple responses on the surface of a magnesium alloy.
[0014] The third object of the present invention is to provide an application of the coating in metal surface modification.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a self-repairing long-lasting coating with multiple responses on the surface of a magnesium alloy, and a preparation method and application thereof. The present invention constructs a composite coating with good inorganic-organic bonding force on the surface of the magnesium alloy, and the in-situ formed Mg(OH) 2 The dopamine molecules containing abundant phenolic hydroxyl groups and amine groups are closely bonded to the magnesium alloy matrix. 2 Under the dual effects of the slightly alkaline environment on the surface and the electric field, a highly adhesive PDA coating was formed. 2It forms strong hydrogen bonds with the outer layer of PCL, thereby forming a three-layer tightly connected composite coating, which effectively isolates the magnesium alloy from direct contact with the environment and improves the corrosion resistance of the magnesium alloy.
[0016] The present invention constructs a long-term composite coating on the surface of the magnesium alloy to warn of corrosion in advance and prevent further corrosion. When the corrosion is about to reach the magnesium alloy substrate, Mg(OH) 2 The coating is destroyed and Mg is released 2+ and OH - , so that the middle layer PDA and the outer layer PCL respond to Mg 2+ and OH - By stimulating the corrosion inhibition effect, the composite coating realizes the efficient protective functions of early warning corrosion and preventing corrosion.
[0017] The present invention constructs a responsive Mg on the surface of magnesium alloy 2+ The self-repairing long-lasting coating will release Mg when the coating is damaged and the magnesium alloy corrodes. 2+ The middle layer PDA contains many phenolic hydroxyl groups (-OH) that can react with Mg 2+ Coordinated to produce a polymer-metal complex (PDA-Mg) that can fill crack protection coatings.
[0018] The present invention constructs a pH-responsive self-repairing long-lasting coating on the surface of the magnesium alloy. When the coating is damaged and the magnesium alloy corrodes and cracks are generated, the released OH - By enhancing the alkalinity of the environment, PCL decomposes under alkaline conditions to release DA in the nanoparticles AgNR@MSN@DA. DA polymerizes into PDA in response to pH and re-forms strong hydrogen with PCL or re-polymerizes with the electrophoretically deposited intermediate layer PDA to repair cracks, thereby preventing further corrosion.
[0019] The present invention constructs a NIR-responsive self-repairing long-lasting coating on the surface of the magnesium alloy. When irradiated by NIR, the photosensitizers PDA and AgNR@MSN@DA exert a photothermal response effect, prompting the coating temperature to rise rapidly. The higher temperature causes the PCL to melt and flow to repair cracks, thereby delaying the corrosion of the magnesium alloy and prolonging the protective effect of the coating.
[0020] The present invention constructs a coating containing AgNR@MSN@DA nanoparticles on the surface of magnesium alloy. MSN can control the Ag + The slow release of DA makes the pH-NIR responsive coating more effective. AgNR can cooperate with PDA as a photothermal responsive agent to increase the temperature of the coating under NIR irradiation, thus achieving the photothermal anti-corrosion and photothermal deicing effects of the coating. + It can effectively kill bacteria and prevent biofouling from colonizing and accumulating on the hull, opening up a new way for marine anti-fouling. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the preparation process of multi-responsive self-repairing long-lasting coating on magnesium alloy surface.
[0022] Figure 2 SEM images of (a) AgNR and (b) AgNR@MSN prepared in Example 1.
[0023] Figure 3 (a) magnesium alloy ZK61, (b) ZK61 / Mg(OH) 2 (c) ZK61 / Mg(OH) 2 / PDA and (d)ZK61 / Mg(OH) 2 SEM image of / PDA / PCL.
[0024] Figure 4 Polarization curves of magnesium alloy ZK61 and each coating sample.
[0025] Figure 5 For coating (a) Mg(OH) 2 / PDA / pure PCL and (b)Mg(OH) 2 Photothermal properties of / PDA / PCL.
[0026] Figure 6 For coating Mg(OH) 2 Thermal imaging images of / PDA / PCL.
[0027] Figure 7 For coating Mg(OH) 2 / PDA / PCL photothermal stability.
[0028] Figure 8 For coatings with scratches (a) Mg(OH) 2 / PDA / PCL, (b)Mg(OH) 2 Optical images of (a) / PDA / pure PCL and (b) pure PCL before and after NIR irradiation.
[0029] Fig. 9 For the coating containing scratches Mg(OH) 2 Experimental phenomena of the galvanic cell of / PDA / PCL before (a) and after (b) NIR irradiation. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.
[0031] The present invention divides the coating with the function of repairing damage into a functional repair coating and a shape repair coating. The functional repair coating restores the protective ability of the coating by loading corrosion inhibitors; the shape repair coating repairs the morphology and structure of the coating by reversible reaction of polymers, chemical bond reorganization and shape memory effect. The long-term coating with the function of repairing damage can repair the surface damage of the coating in time when the coating is damaged, and restore the long-term protective effect of the coating, which has great research value and economic benefits in magnesium alloy protection.
[0032] The present invention aims to provide a self-repairing long-lasting coating with multiple responses on the surface of a magnesium alloy and a preparation method and application thereof. The method comprises subjecting the magnesium alloy to a hydrothermal reaction to obtain an in-situ grown Mg(OH) 2 ; in Mg(OH) 2 A layer of polydopamine (PDA) is electrophoretically deposited on the surface; a layer of polycaprolactone (PCL) containing nanoparticles is spin-coated on the surface of PDA; the nanoparticles are AgNR@MSN@DA nanoparticles that are silver nanorods (AgNR) wrapped with silica (MSN) and loaded with dopamine (DA). The present invention constructs a Mg(OH)-based nanostructured ... 2 Early warning, response Mg 2+ , pH and near-infrared light (NIR) to achieve a long-lasting and stable multi-protection inorganic-organic composite coating with good bonding force. This coating not only has a long-lasting anti-corrosion function, but also has de-icing and marine anti-fouling functions.
[0033] To achieve the above object, the first aspect of the present invention provides a method for preparing a multi-responsive self-repairing long-lasting coating on a magnesium alloy surface, comprising the following steps: The hydrothermal reaction was carried out on the surface of magnesium alloy to obtain in-situ grown Mg(OH) 2 ; In situ grown Mg(OH) 2 Polydopamine was electrophoretically deposited on the surface; preparing nanoparticles of silver nanorods wrapped in silica and loaded with dopamine; uniformly dispersing the nanoparticles in a polycaprolactone solution to obtain a polycaprolactone solution containing the nanoparticles; A polycaprolactone solution containing nanoparticles is coated on polydopamine to prepare a multi-responsive self-repairing long-lasting coating on the surface of a magnesium alloy.
[0034] The present invention constructs an inorganic-organic composite coating with good bonding strength on the surface of the magnesium alloy, and the in-situ formed Mg(OH) 2 The dopamine molecules containing abundant phenolic hydroxyl groups and amine groups are closely bonded to the magnesium alloy matrix. 2 Under the dual effects of the slightly alkaline environment on the surface and the electric field, a highly adhesive PDA coating was formed. 2It forms strong hydrogen bonds with the outer layer of PCL, thereby forming a three-layer tightly connected composite coating, which effectively isolates the magnesium alloy from direct contact with the environment and improves the corrosion resistance of the magnesium alloy.
[0035] The present invention constructs a coating containing AgNR@MSN@DA nanoparticles on the surface of magnesium alloy. MSN can control the Ag + The slow release of DA makes the pH-NIR responsive coating more effective. AgNR can cooperate with PDA as a photothermal responsive agent to increase the temperature of the coating under NIR irradiation, thus achieving the photothermal anti-corrosion and photothermal deicing effects of the coating. + It can effectively kill bacteria and prevent biofouling from colonizing and accumulating on the hull, opening up a new way for marine anti-fouling.
[0036] When the hydrothermal reaction is carried out on the surface of the magnesium alloy, the concentration of the hydrothermal solution is 0.001~0.1 g / mL of NaOH solution, the temperature is 80~160 °C, and the reaction time is 1~12 h.
[0037] In situ grown Mg(OH) 2 When polydopamine is electrophoretically deposited on a substrate, the electrophoresis solution is a 1-10 mg / mL DA solution, and the solvent of the DA solution is deionized water; During electrophoretic deposition, the distance between the anode and cathode is 8-15 mm and the applied current is 2-6 mA / cm 2 The electrophoretic deposition time is 1-10 min; the in-situ grown Mg(OH) 2 of magnesium alloy as cathode.
[0038] In the polycaprolactone solution containing nanoparticles, the polycaprolactone concentration is 1-20 wt %; the nanoparticle concentration is 1-30 mg / mL; The polycaprolactone solution is prepared by dissolving polycaprolactone in one or more of dichloromethane, chloroform and acetone.
[0039] When the polycaprolactone solution containing nanoparticles is coated on the polydopamine, the coating is performed by spin coating, wherein during the spin coating, the spin coating is kept at a low speed of 200-800 rpm and a high speed of 1000-3000 rpm for 10-90 s respectively.
[0040] The silica-wrapped silver nanorods and dopamine-loaded nanoparticles include nanoparticles formed with silica as a shell, silver nanorods as a core, and dopamine as a pore carrier; wherein the length of the silver nanorods is 100-120 nm, and the aspect ratio is 4.16±0.13; The thickness of the silica shell is 10-80 nm; The dopamine loading rate is 5-95% by mass.
[0041] Before the hydrothermal reaction of the magnesium alloy surface, the magnesium alloy surface is pretreated, including: grinding the magnesium alloy surface with sandpaper, and then ultrasonically treating the magnesium alloy with acetone and anhydrous ethanol for 5 to 15 minutes respectively.
[0042] The magnesium alloy includes AZ series, ZK series, WE series or JDBM magnesium alloy.
[0043] In one embodiment, a method for preparing a multi-responsive self-repairing long-lasting coating on a magnesium alloy surface comprises the following steps: Step 1: Pre-treat the magnesium alloy by grinding the surface of the magnesium alloy with sandpaper, and then ultrasonically treat the magnesium alloy with acetone and anhydrous ethanol respectively.
[0044] Step 2: The magnesium alloy is subjected to a hydrothermal reaction to obtain in-situ grown Mg(OH) 2 Prepare a NaOH solution, place the treated magnesium alloy in a reactor containing the NaOH solution, place the reactor in an oven for reaction, take out the sample after the reaction, rinse with deionized water and air dry naturally.
[0045] Step 3: In Mg(OH) 2 A layer of PDA was deposited on the surface by electrophoresis. Prepare DA solution and stir evenly to obtain electrophoresis solution; use constant current mode in a solution containing Mg(OH) 2 The coating was deposited on the surface of the coated magnesium alloy, and then the sample was taken out and placed in a cool place to dry naturally.
[0046] Step 4: Synthesize silica-coated silver nanorod (AgNR@MSN) nanoparticles. This includes the following steps: ① Preparation of AgNR by gold seed method; ② Preparation of core-shell structured nanoparticles AgNR@MSN by sol-gel method; Exemplarily, the specific preparation method of AgNR prepared by the gold seed method is as follows: 1.1) At room temperature, CTAC (50 mM, 8.95 mL), citric acid (5 mM, 1 mL) and HAuCl were added to the solution in sequence. 4 (50 mM, 0.05 mL), and then sodium borohydride (25 mM, 0.25 mL) was used to rapidly reduce HAuCl 4 After 2 min, the bottle cap was closed and the seed solution was heated at 80 °C for 90 min to obtain a gold seed solution.
[0047] 1.2) Add the gold seed solution (1 mL) to a solution containing CTAB (20 mL, 100 mM), HAuCl 4 (0.2 mL, 50 mM), AgNO 3 The gold bipyramids were prepared by adding 1% MgCl (0.2 mL, 10 mM), HCl (0.4 mL, 1 M) and ascorbic acid (AA) (0.16 mL, 100 mM) into the growth aqueous solution. The mixture was allowed to stand at 30 °C for 4 h to obtain the gold bipyramids. After 4 h of reaction, the solution was centrifuged (10000 rpm, 30 min) to remove excess reagents and redispersed in CTAC (10 mM, 1 mL).
[0048] 1.3) Under vigorous stirring, AgNO 3 The solution of Ag (10 mM) and AA (100 mM) was added to the solution of CTAC (10 mM) in gold bipyramid (10 mL) at room temperature. During the whole addition process, the molar ratio [AA]∶[Ag + ] = 4 remained constant. After the addition was completed, the mixture was vigorously stirred at 60 °C for 2 h. Finally, the resulting solution was centrifuged (10000 rpm, 30 min) and redispersed in water to obtain AgNR.
[0049] Exemplarily, the specific preparation method of the core-shell structured nanoparticles AgNR@MSN prepared by the sol-gel method is as follows: 2.1) Add CHCl to the prepared AgNR solution 3 The solution was prepared into a mixed solution with a concentration of 5 mg / mL, to which CTAB solution (5 mM, 2 mL) was added under vigorous stirring and mixed evenly. Subsequently, the mixture was moved to 65 °C and heated for 20 min to remove CHCl 3 , and add it to 86 mL of an aqueous solution containing CTAB (1.5 mM) and NaOH (16 mM, 0.7 mL) at room temperature and mix well.
[0050] 2.2) The above solution was transferred to 80 °C, and 1 mL of TEOS was slowly added dropwise under vigorous stirring and allowed to react for 2 h. After the reaction was completed, the excess reagent was removed by centrifugation (10,000 rpm, 10 min) and the product was collected. The sample was added to a solution containing NH 4 NO 3 The product was extracted with an ethanol solution (6 g / L) for 24 h to remove the remaining template in the product. After the extraction, the product was washed alternately with deionized water and anhydrous ethanol for 6 times, and then collected and dried to obtain mesoporous nanoparticles AgNR@MSN with a core-shell structure.
[0051] Step 5: AgNR@MSN nanoparticles with core-shell mesoporous structure loaded with DA. Prepare a DA solution of a certain concentration, and add 10 mg of core-shell nanoparticles AgNR@MSN into the DA solution; after gently stirring the solution for 24 h, centrifuge the DA-loaded solution (10,000 rpm, 10 min) to remove the supernatant, collect the product and dry it to obtain silica-wrapped silver nanorods and dopamine-loaded nanoparticles (AgNR@MSN@DA).
[0052] Step 6: Spin-coat a layer of PCL containing nanoparticles AgNR@MSN@DA on the PDA surface. Prepare PCL solution with acetone as solvent; add AgNR@MSN@DA nanoparticles with core-shell mesoporous structure to the PCL solution, and disperse the nanoparticles evenly in the solution by ultrasound; take the PCL solution containing nanoparticles and drop it on the sample surface, then stay for a certain period of time at the low speed stage and the high speed stage respectively, and take out the sample after the spin coating is completed and let it air dry naturally.
[0053] A second aspect of the present invention provides a self-repairing long-lasting coating with multiple responses on the surface of a magnesium alloy.
[0054] The third aspect of the present invention provides an application of a coating in metal surface modification. It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0055] Example 1 Preparation method of multi-response long-lasting coating on magnesium alloy ZK61 surface, see Figure 1 As shown, the following steps are included: Step 1: Pre-treat the magnesium alloy ZK61. Use 600#, 1000#, 1500#, and 2000# sandpaper to polish the surface of the magnesium alloy, and then use acetone and anhydrous ethanol to ultrasonically treat the magnesium alloy for 10 min each.
[0056] Step 2: The magnesium alloy ZK61 is subjected to a hydrothermal reaction to obtain in-situ grown Mg(OH) 2 First, prepare a NaOH solution with a concentration of 0.1 g / mL; place the treated ZK61 in a reactor containing 50 mL of NaOH solution; place the reactor in an oven at 80 °C for 3 h; after the reaction, take out ZK61, rinse it with deionized water and air dry it naturally.
[0057] Step 3: In Mg(OH) 2 A layer of PDA was deposited by electrophoresis on the surface. A 2 mg / mL DA solution was prepared and stirred for 10 min; a constant current mode was used in a solution containing Mg(OH) 2The coating was deposited on the ZK61 surface. The distance between the anode 316L stainless steel and the cathode ZK61 was 10 mm, the deposition time was 3 min, and the deposition current was 4 mA / cm 2 ; Then, take out ZK61 and place it in a cool place to dry naturally.
[0058] Step 4: Preparation of core-shell structured mesoporous nanoparticles AgNR@MSN.
[0059] Step 5: Loading DA on the core-shell mesoporous AgNR@MSN nanoparticles, including: preparing a DA solution with a concentration of 10 mg / mL, doping 10 mg of core-shell structured nanoparticles AgNR@MSN into the DA solution, and gently stirring the solution for 24 h; centrifuging the solution (10000 rpm, 10 min) and then drying and collecting the product.
[0060] Step 6: Spin-coat a layer of PCL containing nanoparticles on the surface of PDA. Use acetone as solvent to prepare a 10 wt% PCL solution; add core-shell AgNR@MSN@DA nanoparticles to the PCL solution, the concentration of the nanoparticles is 10 mg / mL, and ultrasonicate for 5 min to evenly disperse the solution; obtain a PCL solution containing nanoparticles; 500 μL of PCL solution containing nanoparticles was dropped on the sample surface, and then kept at 500 rpm for 10 s at the low speed stage and 2000 rpm for 10 s at the high speed stage. After the spin coating, the sample was taken out and air-dried naturally.
[0061] Example 1 uses a single variable method to explore the effects of hydrothermal solvent concentration, hydrothermal temperature and hydrothermal time on the anti-corrosion ability of a multi-responsive self-repairing long-lasting coating prepared on the surface of magnesium alloy ZK61.
[0062] Example 1-1 Same as Example 1, except that Step 2: The magnesium alloy ZK61 is subjected to a hydrothermal reaction to obtain in-situ grown Mg(OH) 2 First, prepare a NaOH solution with a concentration of 0.05 g / mL; place the treated ZK61 in a reactor containing 50 mL of NaOH solution; place the reactor in an oven at 120 °C for 7 h; after the reaction, take out ZK61, rinse it with deionized water and air dry it naturally.
[0063] Example 1-2 Same as Example 1, except that Step 2: The magnesium alloy ZK61 is subjected to a hydrothermal reaction to obtain in-situ grown Mg(OH) 2First, prepare a NaOH solution with a concentration of 0.001 g / mL; place the treated ZK61 in a reactor containing 50 mL of NaOH solution; place the reactor in an oven at 160 °C for 12 h; after the reaction, take out ZK61, rinse it with deionized water and air dry it naturally.
[0064] Example 2 A method for preparing a multi-response long-lasting coating on the surface of magnesium alloy ZK61 comprises the following steps: Step 1: Pre-treat the magnesium alloy ZK61. Use 600#, 1000#, 1500#, and 2000# sandpaper to polish the surface of the magnesium alloy, and then use acetone and anhydrous ethanol to ultrasonically treat the magnesium alloy for 10 min each.
[0065] Step 2: The magnesium alloy ZK61 is subjected to a hydrothermal reaction to obtain in-situ grown Mg(OH) 2 First, prepare a NaOH solution with a concentration of 0.1 g / mL; place the treated ZK61 in a reactor containing 50 mL of NaOH solution; place the reactor in an oven at 120 °C for 3 h; after the reaction, take out ZK61, rinse it with deionized water and air dry it naturally.
[0066] Step 3: In Mg(OH) 2 A layer of PDA was deposited by electrophoresis on the surface. A 2 mg / mL DA solution was prepared and stirred for 10 min; a constant current mode was used in a solution containing Mg(OH) 2 The coating was deposited on the surface of ZK61 with a distance of 10 mm between the anode 316L stainless steel and the cathode ZK61, a deposition time of 1 min, and a deposition current of 2 mA / cm 2 ; Then, take out the sample and place it in a cool place to dry naturally.
[0067] Step 4: Preparation of core-shell structured mesoporous nanoparticles AgNR@MSN.
[0068] Step 5: Loading DA on the core-shell mesoporous AgNR@MSN nanoparticles, including: preparing a DA solution with a concentration of 10 mg / mL, doping 10 mg of core-shell structured nanoparticles AgNR@MSN into the DA solution, and gently stirring the solution for 24 h; centrifuging the solution (10000 rpm, 10 min) and then drying and collecting the product.
[0069] Step 6: Spin-coat a layer of PCL containing nanoparticles on the surface of PDA. Use acetone as solvent to prepare a 10 wt% PCL solution; add core-shell AgNR@MSN@DA nanoparticles to the PCL solution, the concentration of the nanoparticles is 10 mg / mL, and ultrasonicate for 5 min to evenly disperse the solution; obtain a PCL solution containing nanoparticles; 500 μL of PCL solution containing nanoparticles was dropped on the sample surface, and then kept at 500 rpm for 10 s at the low speed stage and 2000 rpm for 10 s at the high speed stage. After the spin coating, the sample was taken out and air-dried naturally.
[0070] Example 2 uses a single variable method to explore the effects of electrophoretic solution concentration, electrophoretic deposition time and electrophoretic deposition current on the anti-corrosion ability of a multi-response self-repairing long-lasting coating prepared on the surface of magnesium alloy ZK61.
[0071] Example 2-1 Same as Example 2, except that Step 3: In Mg(OH) 2 A layer of PDA was deposited on the surface by electrophoresis. A 5 mg / mL DA solution was prepared and stirred for 10 min; a constant current mode was used in a solution containing Mg(OH) 2 The coating was deposited on the ZK61 surface. The distance between the anode 316L stainless steel and the cathode ZK61 was 10 mm, the deposition time was 3 min, and the deposition current was 4 mA / cm 2 ; Then, take out the sample and place it in a cool place to dry naturally.
[0072] Example 2-2 Same as Example 2, except that Step 3: In Mg(OH) 2 A layer of PDA was deposited by electrophoresis on the surface. A 10 mg / mL DA solution was prepared and stirred for 10 min; a constant current mode was used in a solution containing Mg(OH) 2 The coating was deposited on the surface of ZK61 with a distance of 10 mm between the anode 316L stainless steel and the cathode ZK61, a deposition time of 5 min, and a deposition current of 6 mA / cm 2 ; Then, take out the sample and place it in a cool place to dry naturally.
[0073] Example 3 A method for preparing a multi-response long-lasting coating on the surface of magnesium alloy ZK61 comprises the following steps: Step 1: Pre-treat the magnesium alloy ZK61. Use 600#, 1000#, 1500#, and 2000# sandpaper to polish the surface of the magnesium alloy, and then use acetone and anhydrous ethanol to ultrasonically treat the magnesium alloy for 10 min each.
[0074] Step 2: The magnesium alloy ZK61 is subjected to a hydrothermal reaction to obtain in-situ grown Mg(OH) 2 First, prepare a NaOH solution with a concentration of 0.1 g / mL; place the treated ZK61 in a reactor containing 50 mL of NaOH solution; place the reactor in an oven at 120 °C for 3 h; after the reaction, take out ZK61, rinse it with deionized water and air dry it naturally.
[0075] Step 3: In Mg(OH) 2 A layer of PDA was deposited by electrophoresis on the surface. A 2 mg / mL DA solution was prepared and stirred for 10 min; a constant current mode was used in a solution containing Mg(OH) 2 The coating was deposited on the ZK61 surface. The distance between the anode 316L stainless steel and the cathode ZK61 was 10 mm, the deposition time was 3 min, and the deposition current was 4 mA / cm 2 ; Then, take out the sample and place it in a cool place to dry naturally.
[0076] Step 4: Preparation of core-shell structured mesoporous nanoparticles AgNR@MSN.
[0077] Step 5: Core-shell mesoporous AgNR@MSN nanoparticles are loaded with DA. A DA solution with a concentration of 10 mg / mL is prepared. 10 mg of core-shell structured nanoparticles AgNR@MSN are added to the DA solution and the solution is gently stirred for 24 h. The solution is centrifuged (10000 rpm, 10 min) and then dried to collect the product.
[0078] Step 6: Spin-coat a layer of PCL containing nanoparticles on the surface of PDA. Use acetone as solvent to prepare a 5 wt% PCL solution; add core-shell structured AgNR@MSN@DA nanoparticles to the PCL solution, the concentration of the nanoparticles is 10 mg / mL, and ultrasonicate for 5 min to evenly disperse the solution; obtain a PCL solution containing nanoparticles; 500 μL of PCL solution containing nanoparticles was dropped on the sample surface, and then kept at 500 rpm for 10 s at the low speed stage and 2000 rpm for 10 s at the high speed stage. After the spin coating, the sample was taken out and air-dried naturally.
[0079] Example 3 uses a single variable method to explore the effect of PCL solution concentration on the anti-corrosion ability of a multi-responsive self-repairing long-lasting coating made on the surface of magnesium alloy ZK61.
[0080] Example 3-1 Same as Example 3, except that Step 6: Spin-coat a layer of PCL containing nanoparticles on the surface of PDA. Prepare a 10 wt% PCL solution using acetone as solvent; add core-shell AgNR@MSN@DA nanoparticles to the PCL solution, the concentration of the nanoparticles is 10 mg / mL, and ultrasonicate for 5 min to evenly disperse the solution; obtain a PCL solution containing nanoparticles.
[0081] Example 3-2 Same as Example 3, except that Step 6: Spin-coat a layer of PCL containing nanoparticles on the surface of PDA. Prepare a 20 wt% PCL solution using acetone as solvent; add core-shell AgNR@MSN@DA nanoparticles to the PCL solution, the concentration of the nanoparticles is 10 mg / mL, and ultrasonicate for 5 min to evenly disperse the solution; obtain a PCL solution containing nanoparticles.
[0082] Example 4 A method for preparing a multi-response long-lasting coating on the surface of magnesium alloy ZK61 comprises the following steps: Step 1: Pre-treat the magnesium alloy ZK61. Use 600#, 1000#, 1500#, and 2000# sandpaper to polish the surface of the magnesium alloy, and then use acetone and anhydrous ethanol to ultrasonically treat the magnesium alloy for 10 min each.
[0083] Step 2: The magnesium alloy ZK61 is subjected to a hydrothermal reaction to obtain in-situ grown Mg(OH) 2 First, prepare a NaOH solution with a concentration of 0.1 g / mL; place the treated ZK61 in a reactor containing 50 mL of NaOH solution; place the reactor in an oven at 120 °C for 3 h; after the reaction, take out ZK61, rinse it with deionized water and air dry it naturally.
[0084] Step 3: In Mg(OH) 2 A layer of PDA was deposited by electrophoresis on the surface. A 2 mg / mL DA solution was prepared and stirred for 10 min; a constant current mode was used in a solution containing Mg(OH) 2 The coating was deposited on the ZK61 surface. The distance between the anode 316L stainless steel and the cathode ZK61 was 10 mm, the deposition time was 3 min, and the deposition current was 4 mA / cm 2 ; Then, take out the sample and place it in a cool place to dry naturally.
[0085] Step 4: Preparation of core-shell structured mesoporous nanoparticles AgNR@MSN.
[0086] Step 5: Core-shell mesoporous AgNR@MSN nanoparticles are loaded with DA. A DA solution with a concentration of 10 mg / mL is prepared. 10 mg of core-shell structured nanoparticles AgNR@MSN are added to the DA solution and the solution is gently stirred for 24 h. The solution is centrifuged (10000 rpm, 10 min) and then dried to collect the product.
[0087] Step 6: Spin-coat a layer of PCL containing nanoparticles on the PDA surface. Prepare a 10 wt% PCL solution using acetone as solvent; add core-shell AgNR@MSN@DA nanoparticles to the PCL solution at a concentration of 10 mg / mL, and ultrasonicate for 5 min to evenly disperse the solution; take 500 µL of the PCL solution containing nanoparticles and drop it on the sample surface, then stay at 800 rpm in the low speed stage and 3000 rpm in the high speed stage for 10 s respectively, and take out the sample after spin coating and let it air dry naturally.
[0088] Example 4 uses a single variable method to explore the effects of spin coating speed and spin coating time on the uniformity of a multi-response self-repairing long-lasting coating formed on the surface of magnesium alloy ZK61.
[0089] Example 4-1 Same as Example 4, except that, Step 6: Spin-coat a layer of PCL containing nanoparticles on the PDA surface. Prepare a 10 wt% PCL solution using acetone as solvent; add core-shell AgNR@MSN@DA nanoparticles to the PCL solution at a concentration of 10 mg / mL, and ultrasonicate for 5 min to evenly disperse the solution; take 500 µL of the PCL solution containing nanoparticles and drop it on the sample surface, then stay at 200 rpm at a low speed and 1000 rpm at a high speed for 30 s respectively, and take out the sample after spin coating and let it air dry naturally.
[0090] Example 4-2 Same as Example 4, except that, Step 6: Spin-coat a layer of PCL containing nanoparticles on the PDA surface. Prepare a 10 wt% PCL solution using acetone as solvent; add core-shell AgNR@MSN@DA nanoparticles to the PCL solution at a concentration of 10 mg / mL, and ultrasonicate for 5 min to evenly disperse the solution; take 500 µL of the PCL solution containing nanoparticles and drop it on the sample surface, then stay at 500 rpm at a low speed and 2000 rpm at a high speed for 60 s respectively, and take out the sample after spin coating and let it air dry naturally.
[0091] Example 4-3 Same as Example 4, except that, Step 6: Spin-coat a layer of PCL containing nanoparticles on the PDA surface. Prepare a 10 wt% PCL solution using acetone as solvent; add core-shell AgNR@MSN@DA nanoparticles to the PCL solution at a concentration of 10 mg / mL, and ultrasonicate for 5 min to evenly disperse the solution; take 500 µL of the PCL solution containing nanoparticles and drop it on the sample surface, then stay at 800 rpm in the low speed stage and 3000 rpm in the high speed stage for 90 s respectively, and take out the sample after spin coating and let it air dry naturally.
[0092] Example 5 A method for preparing a multi-response long-lasting coating on the surface of magnesium alloy ZK61 comprises the following steps: Step 1: Pre-treat the magnesium alloy ZK61. Use 600#, 1000#, 1500#, and 2000# sandpaper to polish the surface of the magnesium alloy, and then use acetone and anhydrous ethanol to ultrasonically treat the magnesium alloy for 10 min each.
[0093] Step 2: The magnesium alloy ZK61 is subjected to a hydrothermal reaction to obtain in-situ grown Mg(OH) 2 First, prepare a NaOH solution with a concentration of 0.1 g / mL; place the treated ZK61 in a reactor containing 50 mL of NaOH solution; place the reactor in an oven at 120 °C for 3 h; after the reaction, take out ZK61, rinse it with deionized water and air dry it naturally.
[0094] Step 3: In Mg(OH) 2 A layer of PDA was deposited by electrophoresis on the surface. A 2 mg / mL DA solution was prepared and stirred for 10 min; a constant current mode was used in a solution containing Mg(OH) 2 The coating was deposited on the ZK61 surface. The distance between the anode 316L stainless steel and the cathode ZK61 was 10 mm, the deposition time was 3 min, and the deposition current was 4 mA / cm 2 ; Then, take out the sample and place it in a cool place to dry naturally.
[0095] Step 4: Preparation of core-shell structured mesoporous nanoparticles AgNR@MSN.
[0096] Step 5: Core-shell mesoporous AgNR@MSN nanoparticles are loaded with DA. A DA solution with a concentration of 2 mg / mL is prepared. 10 mg of core-shell structured nanoparticles AgNR@MSN are added to the DA solution and the solution is gently stirred for 6 h. The solution is centrifuged (10000 rpm, 10 min) and then dried to collect the product.
[0097] Step 6: Spin-coat a layer of PCL containing nanoparticles on the PDA surface. Prepare a 10 wt% PCL solution using acetone as solvent; add core-shell AgNR@MSN@DA nanoparticles to the PCL solution at a concentration of 10 mg / mL, and ultrasonicate for 5 min to evenly disperse the solution; take 500 µL of the PCL solution containing nanoparticles and drop it on the sample surface, then stay at 500 rpm for 10 s at the low speed stage and 2000 rpm for 10 s at the high speed stage, and take out the sample after spin coating and let it air dry naturally.
[0098] Example 5 uses a single variable method to explore the effect of the amount of DA loaded on the nanoparticles AgNR@MSN on the anti-corrosion ability of the multi-responsive self-repairing long-lasting coating prepared on the surface of the magnesium alloy ZK61.
[0099] Example 5-1 Same as Example 5, except that Step 5: Core-shell mesoporous AgNR@MSN nanoparticles are loaded with DA. A DA solution with a concentration of 10 mg / mL is prepared. 10 mg of core-shell structured nanoparticles AgNR@MSN are added to the DA solution and the solution is gently stirred for 12 h. The solution is centrifuged (10,000 rpm, 10 min) and then dried to collect the product.
[0100] Example 5-2 Same as Example 5, except that Step 5: Core-shell mesoporous AgNR@MSN nanoparticles are loaded with DA. A DA solution with a concentration of 20 mg / mL is prepared. 10 mg of core-shell structured nanoparticles AgNR@MSN are added to the DA solution and the solution is gently stirred for 24 h. The solution is centrifuged (10,000 rpm, 10 min) and then dried to collect the product.
[0101] Example 6 A method for preparing a multi-response long-lasting coating on the surface of magnesium alloy ZK61 comprises the following steps: Step 1: Pre-treat the magnesium alloy ZK61. Use 600#, 1000#, 1500#, and 2000# sandpaper to polish the surface of the magnesium alloy, and then use acetone and anhydrous ethanol to ultrasonically treat the magnesium alloy for 10 min each.
[0102] Step 2: The magnesium alloy ZK61 is subjected to a hydrothermal reaction to obtain in-situ grown Mg(OH) 2 First, prepare a NaOH solution with a concentration of 0.1 g / mL; place the treated ZK61 in a reactor containing 50 mL of NaOH solution; place the reactor in an oven at 120 °C for 3 h; after the reaction, take out ZK61, rinse it with deionized water and air dry it naturally.
[0103] Step 3: In Mg(OH) 2 A layer of PDA was deposited by electrophoresis on the surface. A 2 mg / mL DA solution was prepared and stirred for 10 min; a constant current mode was used in a solution containing Mg(OH) 2 The coating was deposited on the ZK61 surface. The distance between the anode 316L stainless steel and the cathode ZK61 was 10 mm, the deposition time was 3 min, and the deposition current was 4 mA / cm 2 ; Then, take out the sample and place it in a cool place to dry naturally.
[0104] Step 4: Preparation of core-shell structured mesoporous nanoparticles AgNR@MSN.
[0105] Step 5: Core-shell mesoporous AgNR@MSN nanoparticles are loaded with DA. A DA solution with a concentration of 10 mg / mL is prepared. 10 mg of core-shell structured nanoparticles AgNR@MSN are added to the DA solution and the solution is gently stirred for 24 h. The solution is centrifuged (10000 rpm, 10 min) and then dried to collect the product.
[0106] Step 6: Spin-coat a layer of PCL containing nanoparticles on the PDA surface. Use acetone as solvent to prepare a 10 wt% PCL solution; add core-shell AgNR@MSN@DA nanoparticles to the PCL solution, the concentration of the nanoparticles is 0 mg / mL, and ultrasonicate for 5 min to disperse the solution evenly; take 500 µL of PCL solution containing nanoparticles and drop it on the sample surface, then stay at 500 rpm in the low speed stage and 2000 rpm in the high speed stage for 10 s respectively. After the spin coating is completed, take out the sample and air dry it naturally to obtain the multi-responsive long-lasting coating (Mg(OH) 2 / PDA / Pure PCL).
[0107] Example 6 uses the single variable method to explore the effect of the concentration of core-shell structured nanoparticles AgNR@MSN@DA added to the PCL coating on the anti-corrosion ability of the multi-responsive self-repairing long-lasting coating made on the surface of magnesium alloy ZK61.
[0108] Example 6-1 Same as Example 6, except that The concentration of nanoparticles was 5 mg / mL.
[0109] Example 6-2 Same as Example 6, except that The concentration of nanoparticles was 10 mg / mL.
[0110] Example 6-3 Same as Example 6, except that The concentration of nanoparticles was 20 mg / mL.
[0111] Example 7 A method for preparing a multi-response long-lasting coating on the surface of magnesium alloy ZK61 comprises the following steps: Step 1: Pre-treat the magnesium alloy ZK61. Use 600#, 1000#, 1500#, and 2000# sandpaper to polish the surface of the magnesium alloy, and then use acetone and anhydrous ethanol to ultrasonically treat the magnesium alloy for 10 min each.
[0112] Step 2: The magnesium alloy ZK61 is subjected to a hydrothermal reaction to obtain in-situ grown Mg(OH) 2 (ZK61 / Mg(OH) 2 ). First, prepare a NaOH solution with a concentration of 0.1 g / mL; place the treated ZK61 in a reactor containing 50 mL of NaOH solution; place the reactor in an oven at 120 °C for 3 h; after the reaction, take out ZK61, rinse it with deionized water and air dry it naturally.
[0113] Step 3: In Mg(OH) 2 A layer of PDA (ZK61 / Mg(OH) 2 / PDA). Prepare 2 mg / mL DA solution and stir for 10 min; use constant current mode in the presence of Mg(OH) 2 The coating was deposited on the ZK61 surface. The distance between the anode 316L stainless steel and the cathode ZK61 was 10 mm, the deposition time was 3 min, and the deposition current was 4 mA / cm 2 ; Then, take out the sample and place it in a cool place to dry naturally.
[0114] Step 4: Preparation of core-shell structured mesoporous nanoparticles Ag@MSN.
[0115] Step 5: Core-shell mesoporous AgNR@MSN nanoparticles are loaded with DA. A DA solution with a concentration of 10 mg / mL is prepared. 10 mg of core-shell structured nanoparticles AgNR@MSN are added to the DA solution and the solution is gently stirred for 24 h. The solution is centrifuged (10000 rpm, 10 min) and then dried to collect the product.
[0116] Step 6: Spin-coat a layer of PCL containing nanoparticles on the PDA surface. A 10 wt% PCL solution was prepared using acetone as solvent; AgNR@MSN@DA nanoparticles with core-shell structure were added to the PCL solution, with a concentration of 10 mg / mL of nanoparticles, and the solution was evenly dispersed by ultrasonication for 5 min; 500 µL of PCL solution containing nanoparticles was dripped onto the sample surface, and then the sample was kept at a low speed of 500 rpm and a high speed of 2000 rpm for 10 s respectively. After the spin coating was completed, the sample was taken out and naturally air-dried to obtain a multi-responsive long-lasting coating (Mg(OH) 2 / PDA / PCL).
[0117] Example 7 provides a ZK61 magnesium alloy (ZK61 / Mg(OH)2O3) protected by a multi-response self-repairing long-lasting coating obtained by the above preparation method. 2 / PDA / PCL).
[0118] Example 8 A method for preparing a multi-response long-lasting coating on the surface of magnesium alloy AZ31 comprises the following steps: Step 1: Pre-treat the magnesium alloy AZ31. Use 600#, 1000#, 1500#, and 2000# sandpaper to polish the surface of the magnesium alloy, and then use acetone and anhydrous ethanol to ultrasonically treat the magnesium alloy for 10 min each.
[0119] Step 2: The magnesium alloy AZ31 is subjected to a hydrothermal reaction to obtain in-situ grown Mg(OH) 2 First, prepare a NaOH solution with a concentration of 0.1 g / mL; place the treated AZ31 in a reactor containing 50 mL of NaOH solution; place the reactor in an oven at 120 °C for 3 h; after the reaction, take out AZ31, rinse it with deionized water and air dry it naturally.
[0120] Step 3: In Mg(OH) 2 A layer of PDA was deposited by electrophoresis on the surface. A 2 mg / mL DA solution was prepared and stirred for 10 min; a constant current mode was used in a solution containing Mg(OH) 2 The coating was deposited on the AZ31 surface. The distance between the anode 316L stainless steel and the cathode AZ31 was 10 mm, the deposition time was 3 min, and the deposition current was 4 mA / cm 2 ; Then, take out AZ31 and place it in a cool place to dry naturally.
[0121] Step 4: Preparation of core-shell structured mesoporous nanoparticles Ag@MSN.
[0122] Step 5: Loading DA on the core-shell mesoporous AgNR@MSN nanoparticles, including: preparing a DA solution with a concentration of 10 mg / mL, doping 10 mg of core-shell structured nanoparticles AgNR@MSN into the DA solution, and gently stirring the solution for 24 h; centrifuging the solution (10000 rpm, 10 min) and then drying and collecting the product.
[0123] Step 6: Spin-coat a layer of PCL containing nanoparticles on the PDA surface. Prepare a 10 wt% PCL solution using acetone as solvent; add core-shell AgNR@MSN@DA nanoparticles to the PCL solution at a concentration of 10 mg / mL, and ultrasonicate for 5 min to evenly disperse the solution; take 500 µL of the PCL solution containing nanoparticles and drop it on the sample surface, then stay at 500 rpm for 10 s at the low speed stage and 2000 rpm for 10 s at the high speed stage, and take out the sample after spin coating and let it air dry naturally.
[0124] The only difference between Example 8 and Example 7 is the type of magnesium alloy.
[0125] In order to illustrate the relevant performance of the multi-response self-repairing long-lasting coating on the magnesium alloy surface provided by the present invention, see Figures 2~9 As shown, the following is explained.
[0126] Figure 2 SEM images of (a) AgNR and (b) AgNR@MSN prepared in Example 1.
[0127] Figure 2 (a) shows that the length of AgNR is 100-120 nm. Figure 2 In (b), we can see the core-shell structured nanoparticles with the MSN shell layer wrapped around the AgNR.
[0128] Figure 3 (a) ZK61 prepared in Example 7, (b) ZK61 / Mg(OH) 2 (c) ZK61 / Mg(OH) 2 / PDA and (d)ZK61 / Mg(OH) 2 SEM image of / PDA / PCL sample.
[0129] Figure 3 (b) is Mg(OH) 2 The coating along Figure 3 (a) In-situ growth of sandpaper scratches on the surface of magnesium alloy ZK61. Figure 3 In (c), PDA can be seen tightly attached to Mg(OH) 2 The coating covers the scratches. Figure 3In (d), the PCL containing nanoparticles completely covers the scratches, and the entire coating is smooth and uniform.
[0130] Figure 4 The potentiodynamic polarization curves of the coating samples in Example 7 are shown in Table 1. 2 The corrosion current density of ZH-PDA and ZHP-PCL gradually decreased, and they were all lower than that of magnesium alloy ZK61, indicating that the ZHP-PCL composite coating of the present invention greatly improved the corrosion resistance of magnesium alloy. 2 , ZH-PDA, and ZHP-PCL are ZK61 / Mg(OH) 2 、ZK61 / Mg(OH) 2 / PDA, ZK61 / Mg(OH) 2 / PDA / PCL abbreviation.
[0131] Figure 5 The coating Mg(OH) of Example 7 2 / PDA / PCL and Example 6 coating Mg(OH) 2 Photothermal properties of / PDA / pure PCL.
[0132] Figure 5 (a) is the coating Mg(OH) 2 / PDA / pure PCL at different power densities 0.5 W / cm 2 , 1.0 W / cm 2 , 2.0W / cm 2 The temperature change of the coating after 5 min of NIR irradiation with different power densities. NIR with different power densities caused the coating temperature to increase within 5 min. Figure 5 (b) is the coating Mg(OH) 2 / PDA / PCL at different power densities 0.5 W / cm 2 , 1.0 W / cm 2 , 2.0 W / cm 2 Figure 3 shows the temperature change after NIR irradiation for 5 min. The addition of AgNR further increases the coating temperature after NIR irradiation.
[0133] Figure 6 The coating Mg(OH) of Example 7 2 Thermal imaging of PDA / PCL at a power density of 1.0 W / cm 2 Under NIR irradiation, the coating Mg(OH) 2 / PDA / PCL can be heated to the melting point of PCL 60 ℃ within 2 min.
[0134] Figure 7The coating Mg(OH) of Example 7 2 Photothermal stability of / PDA / PCL. Coating Mg(OH) 2 / PDA / PCL at different power densities 0.5 W / cm 2 , 1.0 W / cm 2 , 2.0 W / cm 2 When NIR irradiated, a stable coating temperature change can be achieved, indicating that the coating Mg(OH) 2 / PDA / PCL has stable photothermal performance.
[0135] Figure 8 The scratched coating Mg(OH) of Example 7 and Example 6 2 / PDA / PCL(a)、Mg(OH) 2 Optical images of / PDA / pure PCL (b) and pure PCL with scratches (c) before and after NIR irradiation.
[0136] Figure 8 (a) shows the Mg(OH) coating with scratches 2 / PDA / PCL at a power density of 1.0 W / cm 2 After 10 min of NIR irradiation, the scratches were repaired. This was due to the photothermal effect of PDA and AgNR, which increased the coating temperature to the melting point of PCL, and PCL melted to repair the cracks. Figure 8 (b) shows the Mg(OH) coating with scratches 2 / PDA / pure PCL was repaired due to the photothermal effect of PDA. Figure 8 (c) shows the pure PCL coating with scratches at a power density of 1.0 W / cm 2 The scratches were not repaired after 10 min of NIR irradiation. Pure PCL had no photothermal effect under NIR irradiation, and the coating temperature did not reach the melting point of PCL, so the scratches could not be repaired.
[0137] It should be noted that polydopamine (PDA) is a polymer material formed by the polymerization of dopamine (DA) monomers, and has rich functional groups, such as phenolic hydroxyl groups, amino groups, etc. This chemical structure gives polydopamine the ability to absorb near-infrared light and convert light energy into heat energy under near-infrared light irradiation conditions, thereby producing a photothermal effect.
[0138] Silver nanorods (AgNR) have strong surface plasmon resonance absorption characteristics (SPR) in the near-infrared region. This characteristic enables AgNR to achieve a high photothermal conversion efficiency under near-infrared laser irradiation of a specific wavelength. By adjusting the size and shape of the silver nanorods and controlling their SPR absorption peak to match the laser wavelength, the photothermal effect can be optimized.
[0139] The coating provided by the present invention comprises electrophoretically deposited PDA and AgNR@MSN@DA dispersed in PCL. The photothermal effect of PDA and AgNR (the SPR of the AgNR matches 808 nm) enables the composite coating to rapidly heat up to the melting point of PCL, 60°C, under the irradiation of 808 nm near-infrared light (NIR), and the melting and flow of PCL is used to repair the cracks in the coating.
[0140] Fig. 9 The scratched coating Mg(OH) of Example 7 2 Experimental phenomena of the galvanic cell before and after / PDA / PCL irradiation with NIR.
[0141] Fig. 9 (a) is a scratch coating containing Mg(OH) 2 / PDA / PCL is a primary battery device designed with magnesium alloy ZK61 as the negative electrode and copper rod as the positive electrode. As the coating is scratched, the magnesium alloy ZK61 is corroded, a redox reaction occurs, and the chemical energy is converted into electrical energy to make the diode emit light. Fig. 9 (b) is the scratch coating containing Mg(OH) 2 / PDA / PCL magnesium alloy ZK61 at 1.0W / cm 2 After NIR irradiation repair, the copper rod was used as the negative electrode and the copper rod was used as the positive electrode. It was found that the original battery device was not enough to make the diode emit light. This was because there was not enough chemical energy converted into electrical energy. The damaged coating was repaired and the magnesium alloy ZK61 was protected.
[0142] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a multi-responsive self-repairing long-lasting coating on a magnesium alloy surface, characterized in that: The following steps are involved: A hydrothermal reaction is carried out on the surface of the magnesium alloy to obtain in-situ grown Mg(OH)2; Electrophoretic deposition of polydopamine on in situ grown Mg(OH)2; preparing nanoparticles of silver nanorods wrapped in silica and loaded with dopamine; uniformly dispersing the nanoparticles in a polycaprolactone solution to obtain a polycaprolactone solution containing the nanoparticles; A polycaprolactone solution containing nanoparticles is coated on polydopamine to prepare a multi-responsive self-repairing long-lasting coating on the surface of a magnesium alloy.
2. The method for preparing a multi-response self-repairing long-lasting coating on a magnesium alloy surface according to claim 1, characterized in that: When the hydrothermal reaction is carried out on the surface of the magnesium alloy, the concentration of the hydrothermal solution is 0.001~0.1 g / mL of NaOH solution, the temperature is 80~160 ℃, and the reaction time is 1~12 h.
3. The method for preparing a multi-response self-repairing long-lasting coating on a magnesium alloy surface according to claim 1, characterized in that: When polydopamine was electrophoretically deposited on the in-situ grown Mg(OH)2, the electrophoresis solution was a 1-10 mg / mL DA solution, and the solvent of the DA solution was deionized water; During electrophoretic deposition, the distance between the anode and cathode is 8-15 mm and the applied current is 2-6 mA / cm 2 The electrophoretic deposition time is 1 to 10 min, wherein the magnesium alloy containing in-situ grown Mg(OH)2 is used as the cathode.
4. The method for preparing a multi-responsive self-repairing long-lasting coating on a magnesium alloy surface according to claim 1, characterized in that: In the polycaprolactone solution containing nanoparticles, the polycaprolactone concentration is 1-20 wt %; the nanoparticle concentration is 1-30 mg / mL; The polycaprolactone solution is prepared by dissolving polycaprolactone in one or more of dichloromethane, chloroform and acetone.
5. The method for preparing a multi-response self-repairing long-lasting coating on a magnesium alloy surface according to claim 1, characterized in that: When the polycaprolactone solution containing nanoparticles is coated on the polydopamine, the coating is performed by spin coating, wherein during the spin coating, the spin coating is kept at a low speed of 200-800 rpm and a high speed of 1000-3000 rpm for 10-90 s respectively.
6. The method for preparing a multi-response self-repairing long-lasting coating on a magnesium alloy surface according to claim 1, characterized in that: The silica-wrapped silver nanorods and dopamine-loaded nanoparticles include nanoparticles formed with silica as a shell, silver nanorods as a core, and dopamine as a pore carrier; wherein the length of the silver nanorods is 100-120 nm, and the aspect ratio is 4.16±0.13; The thickness of the silica shell is 10-80 nm; The dopamine loading rate is 5-95% by mass.
7. The method for preparing a multi-response self-repairing long-lasting coating on a magnesium alloy surface according to claim 1, characterized in that: Before the hydrothermal reaction of the magnesium alloy surface, the magnesium alloy surface is pretreated, including: grinding the magnesium alloy surface with sandpaper, and then ultrasonically treating the magnesium alloy with acetone and anhydrous ethanol for 5 to 15 minutes respectively.
8. The method for preparing a multi-response self-repairing long-lasting coating on a magnesium alloy surface according to claim 1, characterized in that: The magnesium alloy includes AZ series, ZK series, WE series or JDBM magnesium alloy.
9. A self-repairing long-lasting coating with multiple responses on the surface of a magnesium alloy obtained by the method according to any one of claims 1 to 8.
10. Use of the coating according to claim 9 in metal surface modification.
Citation Information
Patent Citations
Method for preparing polydopamine film on magnesium and magnesium alloy surfaces through electropolymerization
CN109023462A
Method for preparing corrosion-resistant composite coating by using layer-by-layer self-assembly technology
CN113578706A
Preparation method of degradable orthopedic implant material capable of dual self-healing and controllable drug release
CN114504676A
Preparation method of polylactic acid composite coating on surfaces of magnesium and magnesium alloy
CN118045233A
Preparation method and application of anti-gravity perfusion type electrophoretic deposition coating on surface of porous implant
CN118854411A